Drainage and leaching losses of nitrogen and dissolved organic carbon after introducing maize into a continuous paddy-rice crop rotation - He, Yao; Lehndorff, Eva; Amelung, Wulf; Wassmann, Reiner; Alberto, Ma. Carmelita; von Unold, Georg; Siemens, Jan (Elsevier, 2017)
Farmers in South Asia increasingly switch from continuous paddy-rice cropping to rotations including non-flooded crops, such as growing maize in the dry season. We hypothesized that the introduction of maize into a permanent paddy-rice cropping system boosts drainage and leaching losses of nitrogen (N) and dissolved organic carbon (DOC) in the initial years of maize establishment, due to the disturbance of the equilibrated soil conditions established under continuous paddy cropping. We tested this hypothesis in a 3.5-year field experiment using monolith lysimeters cropped with either (i) single paddy rice in the wet season and maize in the dry season (maize-paddy rice, M-MIX), or (ii) double paddy rice (R-WET) as control. Expandable and compressible pads minimized the formation of a gap at the interface between soil monolith and lysimeter casing during shrinking and swelling of the clay soil. In the first year of introducing maize, drainage (606 l m−2 yr−1) and leaching of total nitrogen (TN, 6.8 g N m−2 yr−1) and DOC (2.7 g m−2 yr−1) were significantly larger in M-MIX than in R-WET (water: 149 l m−2 yr−1, TN: 0.1 g m−2 yr−1, DOC: 0.7 g m−2 yr−1). However, the additional losses of water, nitrogen, and DOC caused by the introduction of maize disappeared in the following years. In the last two dry seasons of our study, drainage and leaching losses of TN, and DOC were even significantly smaller in M-MIX than in R-WET. In the dry seasons of the 2nd to 4th year after introducing maize (2013–2015), M-MIX saved on average 388 l m−2 of percolation water losses compared to R-WET and leaching losses of TN and DOC under maize were reduced on average by 0.6 g m−2 and 1.6 g m−2, respectively. We conclude that leaching losses of water and nutrients are only transiently boosted during the first year after introducing maize in perennial rice cropping systems, so that maize cropping in the dry season could save water and reduce nutrient leaching in comparison to continuous paddy-rice cropping in the long run. Long-term field trials are necessary to validate the lysimeter results